Assignment 14

#$&*

course MTH272

12/10 about 12:15 pm

014.

Note the document qa_ac2_14.htm , which gives an introduction to the logic and mechanics of integration by substitution.

*********************************************

Question: `qQuery problem 6.1.5 (was 6.1.4) integral of (2t-1)/(t^2-t+2)

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

u = t^2 - t + 2 du = 2t - 1 dt

integral (du/u) = ln |u| + c = ln |t^2 - t + 2| + c

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: `a To integrate (2t-1) / (t^2-t+2) use u = t^2 - t + 2. We find that du = (2 t - 1) dt, which is there just waiting for you in the integrand.

This gives you integrand du / u.

The integral is ln | u | + c. Substituting we get

int( (2t-1) / (t^2 - 1 + 2) with respect to t) = ln | t^2 - t + 2 | + c.

The absolute value is important because t^2 - t + 2 can be negative.

STUDENT QUESTION:

Having a hard time still seeing how to get started

INSTRUCTOR RESPONSE

Understood. This is a common problem.

Once you see what to do it's fairly straightforward, but how do you see what needs to be done?

Generally I recommend checking to see if any other part of the integrand has a derivative which is equal to, or a multiple of, a factor of the integrand.

Just what does this mean?

In the present case the integrand is (2t-1)/(t^2-t+2).

What are the factors of the integrand?

The integrand has only one factor, which is (2 t - 1).

What are the 'other parts' of the integrand, and what are their derivatives?

The only thing you have besides the factor (2 t - 1) is the denominator t^2 - t + 2.

The derivative of this 'part' is 2 t - 1.

Do any of those derivatives match any of the factors?

Yes. The derivative is 2 t - 1, and the only factor is 2 t - 1.

If the answer to the above is 'yes', then let u be the part whose derivative is equal to the factor and proceed.

Ok, so u = t^2 - t + 1.

Thus du/dt = 2 t - 1, so du = (2 t - 1) dt.

The expression (2 t - 1) / (t^2 - t + 2) dt has 'numerator' (2 t - 1) dt and denominator u. So the expression can be written du / u.

An antiderivative of du / u is ln | u |, and the general antiderivative is ln | u | + c.

Thus we get our general solution ln | t^2 - t + 2 | + c.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `qQuery problem 6.1.32 (was 6.1.26) integral of 1 / (`sqrt(x) + 1)

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

U = sqrt(x) + 1 x = (u-1)^2 dx = 2(u-1) du

Int. ( (2*(u-1))/u du = 2*int.(u-1)/u du = 2*int.(u/u) du - (1/u) du = 2*int.(1-(1/u) du

2*(u - ln |u|) + c = 2*sqrt.(x) - 2*ln|sqrt(x) + 1| + c

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: `a If we let u = (sqrt x) + 1 we can solve for x to get

x = (u-1)^2 so that

dx = 2(u-1) du.

So the integral of 1 / (`sqrt(x) + 1) dx becomes the integral of (2 ( u - 1 ) / u) du.

Integrating ( u - 1) / u with respect to u we express this as

( u - 1) / u = (u / u) - (1 / u) = 1 - (1 / u). An antiderivative is u - ln | u |.

Substituting u = (sqrt x) + 1 and adding the integration constant c we end up with

(sqrt x) + 1 - ln | (sqrt x) + 1 | + c.

Our integral is of 2 (u-1)/u, double the expression we just integrated, so our result will also be double. We get

2 (sqrt x) + 2 - 2 ln | (sqrt x) + 1 | + c.

Since c is an arbitrary constant, 2 + c is also an arbitrary constant so the final solution can be expressed as

2 (sqrt x) - 2 ln | (sqrt x) + 1 | + c.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `qquery problem 6.1.56 (was 6.1.46) area bounded by x (1-x)^(1/3) and y = 0

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

X=0 (1-x)^(1/3)=0 so x=1

Int. [x*(1-x)^(1/3),x,0,1] u=1-x du=dx x=1-u

Int.[(1-u)*(u)^(1/3),u,0,1]

(3/4)*u^(4/3) - (3/7)*u^(7/3) = (3/4)(1-x)^(4/3) - (3/7)(1-x)^(7/3)

Plug in limits

((3/4)-(3/7)) - (0-0) = 9/28 or approx. 0.321

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: `a Begin by sketching a graph to see that there is a finite region bounded by the graph and by y = 0. Then find the points where the graph crosses the line y = 0 but finding where the expression takes the value 0:

x(1-x)^(1/3) = 0 when x = 0 or when 1-x = 0. Thus the graph intersects the x axis at x = 0 and x = 1.

We therefore integrate x (1-x)^(1/3) from 0 to 1.

We let u = 1-x so du = dx, and x = 1 - u.

This transforms the integrand to (1 - u) * u^(1/3) = u^(1/3) - u^(4/3), which can be integrated term by term, with each term being a power function.

Our antiderivative is 3/4 u^(4/3) - 3/7 u^(7/3), which translates to 3/4 (1-x)^(4/3) - 3/7 ( 1-x)^(7/3).

The result is 9/28 = .321 approx..

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):OK

------------------------------------------------

Self-critique Rating:OK

*********************************************

Question: `qQuery problem P = int(1155/32 x^3(1-x)^(3/2), x, a, b).

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

U=1-x x=1-u

1155/32 * Int.[(1-u)^3*u^(3/2),u,a,b]

1155/32 * Int.[u^(3/2)-3u^(5/2)-3u^(7/2)-u^(9/2)

1155/32 * [(2/5)u^(5/2) - (6/7)u^(7/2) - (2/3)u^(9/2) - (2/11)u^(11/2)]

Subsitite u=1-x

Skip a few steps and simplify

(1-a)^(5/2)*((231-495(1-a)-385(1-a)^2-105(1-a)^3)/16) - (1-b)^(5/2)*(( 231-495(1-b)-385(1-b)^2-105(1-b)^3)/16)

confidence rating #$&*:2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: `a For reference

int(1155/32 x^3(1-x)^(3/2), x, a, b) means 'the integral of 1155 / 32 x^3 ( 1 - x)^(3/2), integrated with respect to x

between limits x = a and x = b'.

That would be written with an integral sign with limits a and b, then 1155/32 x^3(1-x)^(3/2) dx.

It's easiest to integrate if you change the variable to u = 1 - x, which changes the integrand to 1155/32 (1 + u)^3 *

u^(3/2). Expand the cube and multiply through by u^(3/2) to get a sum of four power functions, easily integrated

The result is of course a bit messy:

First we expand the cube: (1 + u)^3 = 1 + 3 u + 3 u^2 + u^3, so

1155/32 ((1 + u)^3)(u^(3/2)) =

1155 / 32 ( 1 + 3 u + 3 u^2 + u^3) * u^(3/2) =

1155 / 32 ( u^(3/2) + 3 u^(5/2) + 3 u^(7/2) + u^(9/2)).

An antiderivative is

1155 / 32 ( 2/5 u^(5/2) + 6/7 u^(7/2) + 6/9 u^(9/2) + 2/11 u^(11/2) ).

Since u = 1 - x the limits on the u integral would be 1 - a and 1 - b.

The result would therefore be

1155 / 32 ( 2/5 (1-b)^(5/2) + 6/7 (1-b)^(7/2) + 6/9 (1-b)^(9/2) + 2/11 (1-b)^(11/2) ) - 1155 / 32 ( 2/5 (1-a)^(5/2) + 6/7 (1-a)^(7/2) + 6/9 (1-a)^(9/2) + 2/11 (1-a)^(11/2) ), which is slightly simplified to

1155 / 32 ( 2/5 (1-b)^(5/2) + 6/7 (1-b)^(7/2) + 6/9 (1-b)^(9/2) + 2/11 (1-b)^(11/2) ) - 2/5 (1-a)^(5/2) - 6/7 (1-a)^(7/2) - 6/9 (1-a)^(9/2) - 2/11 (1-a)^(11/2) ).

Factoring (1 - b)^(5/2) from the first four terms and (1 - a)^(5/2) from the last four terms, and simplifying yields

((1 - a)^(5/2)(105 a^3 + 70 a^2 + 40 a + 16) - (1 - b)^(5/2) (105 b^3 + 70 b^2 + 40 b + 16))/16.

STUDENT COMMENT

I understand the integration but the expanding of the cube is were I got lost.

INSTRUCTOR RESPONSE

Use the distributive and commutative laws to expand the cube:

(1 + u)^3 = (1 + u) * (1 + u) ^2

(1 + u)^2

= (1 + u) ( 1 + u)

= 1 ( 1 + u) + u * (1 + u)

= 1 + u + u + u^2

= u^2 + 2 u + 1, so

(1 + u)^3

= (1 + u) * (1 + u) ^2

= (1 + u) * (u^2 + 2 u + 1)

= 1 * (u^2 + 2 u + 1) + u * (u^2 + 2 u + 1)

= u^2 + 2 u + 1 + u^3 + 2 u^2 + u

= u^3 + 3 u^2 + 3 u + 1.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):My answer does vary slightly for your given solution. I did not that when letting u=1-x you have x=1+u but I have x=1-u which I thought was correct. See if you can sort through what I might have done wrong.

@&

int(1155/32 x^3(1-x)^(3/2), x, a, b)

= ((1 - a)^(5/2)·(105·a^3 + 70·a^2 + 40·a + 16) - (1 - b)^(5/2)·(105·b^3 + 70·b^2 + 40·b + 16))/16

*@

@&

If u = 1 - x, then x = 1 - u so that dx = - du.

The integrand then becomes

-1155 / 32 * (1 - u)^3 u^(3/2) du

and the limits on the integral are

u = 1 - a (corresponding to x = a)

and

u = 1 - b (corresponding to x = b).

The result is

int( -1155/32 ( 1 - u)^3 u^(3/2) du, u from 1-a to 1-b), which comes out

((1 - a)^(5/2)·(105·a^3 + 70·a^2 + 40·a + 16) - (1 - b)^(5/2)·(105·b^3 + 70·b^2 + 40·b + 16))/16

*@

------------------------------------------------

Self-critique Rating:3

*********************************************

Question: `qWhat is the probability that a sample will contain between 0% and 25% iron?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

(-1155/32)*int. (1-u)^3*(u^(3/2) du =

-1155/32 * [(2/5)u^(5/2) - (6/7)u^(7/2) - (2/3)u^(9/2) - (2/11)u^(11/2)]

-1155/32 * [(2/5)(1-x)^(5/2) - (6/7)(1-x)^(7/2) - (2/3)(1-x)^(9/2) - (2/11)(1-x)^(11/2)]

-1155/32 * [(2/5)(1-.25)^(5/2) - (6/7)(1-.25)^(7/2) - (2/3)(1-.25)^(9/2) - (2/11)(1-.25)^(11/2)] - (-1155/32 * [(2/5)(1-0)^(5/2) - (6/7)(1-0)^(7/2) - (2/3)(1-0)^(9/2) - (2/11)(1-0)^(11/2))] = .12.2123 + 47.125 = 34.9127

confidence rating #$&*:2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: `a The probability of an occurrence between 0 and .25 is found by integrating the expression from x = 0 to x = .25:

Let u = 1-x so du = -dx and x = 1-u.

Express in terms of u:

-(1155/32) * int ( (1-u)^3 (u)^(3/2) du )

Expand the integrand:

-(1155/32) * int( (1 - 3 u + 3 u^2 - u^3) * u^(3/2) ) =

-1155/32 * int( u^(3/2) - 3 u^(5/2) + 3 u^(7/2) - u^(9/2) ) .

An antiderivative of u^(3/2) - 3 u^(5/2) + 3 u^(7/2) - u^(9/2) is 2/5 u^(5/2) - 3 * 2/7 u^(7/2) + 3 * 2/9 * u^(9/2) - 2/11 u^(11/2) . So we obtain for the indefinite integral

-1155/32 * ( 2/5 u^(5/2) - 3 * 2/7 u^(7/2) + 3 * 2/9 * u^(9/2) - 2/11 u^(11/2) ).

Express in terms of x:

-1155/32 * ( 2/5 ( 1 - x )^(5/2) - 3 * 2/7 ( 1 - x )^(7/2) + 3 * 2/9 * ( 1 - x )^(9/2) - 2/11 ( 1 - x )^(11/2) )

Evaluate this antiderivative at the limits of integration 0 and .25 .

You get a probability of .0252, approx, which is about 2.52%, for the integral from 0 to .25; this is the probability of a result between 0 and 25%.

To get the probability of a result between 50% and 100% integrate between .50 and 1. You get .736, which is 73.6%

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):I did not see this problem in the text so I relied on the given solution and assumed it was an expansion of the previous problem. I was not sure why 1155/32 was negative but I worked it out like that. I did get a different answer so I am not sure what I did wrong.

------------------------------------------------

Self-critique Rating:3

`qQuery Add comments on any surprises or insights you experienced as a result of this assignment.

???FYI. I know I am pretty far behind right now but I do plan to get everything completed before 12/19. I hope to take Test 3 this Saturday and Test 4 next Tuesday.???"

@&

You appear to have the ability to pull this off, if you have time.

*@

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

&#Good responses. See my notes and let me know if you have questions. &#